La collaboration entre Maurice Denis et Henri Carot à la lumière de la restauration des verrières du Vésinet (Yvelines) - Laurence de Finance; Fabienne Stahl (In Situ)
The realisation of a stained-glass window requires the association of several skills including those of the designer (the ‘cartonnier’ or cartoon painter) and the painter on glass. The restoration of the stained-glass windows of the chapels and ambulatory of the Sainte-Marguerite church at Le Vesinet (Yvelines) allowed for a study of the close collaboration between the painter Maurice Denis and the glass painter Henri Carot. Many documents were brought to light during the restoration project and have been studied: projects, drawings, sketches and two series of full-scale design cartoons. The comparative analysis of these documents allows the creation of the stained-glass to be followed step by step, from the initial project to the final realisation.